Enlaces Químicos y la Formulación de Compuestos Inorgánicos, en la Guía didáctica digital “ESQ” mediante el método del aula invertida, en el aprendizaje de Química General, con estudiantes de segundo semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología. - Tumipamba Cando, Priscila Abigail (2025)
Digital teaching guides and the flipped classroom method are integrated to strengthen the learning process of General Chemistry, addressing challenges such as a lack of interest, motivation, and difficulties in understanding concepts. In this context, this research proposes the creation of the digital guide ESQ, designed using the Genially tool, which focuses on the topics of chemical bonds and the formulation of inorganic compounds. The methodology employed a quantitative approach, featuring a non-experimental and cross-sectional design, a descriptive level, a basic objective, and both field and bibliographic types. For data collection, the survey technique was employed, utilizing its instrument, the questionnaire, which was administered to a population of 38 students after the proposal was disseminated. The results showed that the interactive activities designed in the guide, such as infographics, educational games, and dynamic presentations, generated a high level of interest, creativity, and autonomous learning among students. Likewise, the flipped classroom methodology allowed students to effectively organize and manage their own learning process, consolidating their understanding of key concepts in General Chemistry. In conclusion, the digital guide ESQ is an educational resource that fosters more dynamic, interactive, and meaningful learning, contributing to an educational process adapted to current technological and academic demands.